2017
DOI: 10.1016/j.celrep.2017.06.059
|View full text |Cite
|
Sign up to set email alerts
|

Golgi Outpost Synthesis Impaired by Toxic Polyglutamine Proteins Contributes to Dendritic Pathology in Neurons

Abstract: Dendrite aberration is a common feature of neurodegenerative diseases caused by protein toxicity, but the underlying mechanisms remain largely elusive. Here, we show that nuclear polyglutamine (polyQ) toxicity resulted in defective terminal dendrite elongation accompanied by a loss of Golgi outposts (GOPs) and a decreased supply of plasma membrane (PM) in Drosophila class IV dendritic arborization (da) (C4 da) neurons. mRNA sequencing revealed that genes downregulated by polyQ proteins included many secretory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 49 publications
(64 reference statements)
2
53
0
Order By: Relevance
“…For example, Richards et al ( 9 ) showed that dendrite defects were associated with perturbations of the Rab11-dependent endosomal recycling system in a Drosophila model of Huntington’s disease. In addition, we previously demonstrated that dendrite defects were associated with perturbed actin cytoskeletal structure and impaired subcellular distribution of Golgi outposts in Drosophila models of SCA type 3 (SCA3), also known as Machado–Joseph disease (MJD) ( 10 , 11 ). Despite these efforts, the molecular mechanism of polyQ protein toxicity and the link to the resulting dendrite pathology remain largely unknown.…”
mentioning
confidence: 99%
“…For example, Richards et al ( 9 ) showed that dendrite defects were associated with perturbations of the Rab11-dependent endosomal recycling system in a Drosophila model of Huntington’s disease. In addition, we previously demonstrated that dendrite defects were associated with perturbed actin cytoskeletal structure and impaired subcellular distribution of Golgi outposts in Drosophila models of SCA type 3 (SCA3), also known as Machado–Joseph disease (MJD) ( 10 , 11 ). Despite these efforts, the molecular mechanism of polyQ protein toxicity and the link to the resulting dendrite pathology remain largely unknown.…”
mentioning
confidence: 99%
“…Transcriptional and epigenetic alterations have been shown to contribute to the broad spectrum of neuronal phenotypes ranging from early neuropathic features to late-stage neuronal cell death in polyQ diseases [ 31 ]. For instance, recent studies showed that polyQ proteins induced early changes to the dendrite morphology through the perturbation of RNA granule formation and transcriptional cascades regulating the ER-to-Golgi (COPII) pathway [ 37 39 ]. In the SCA1 mouse model, the translational repressor Capicua was shown to be critically involved [ 40 ], and in HD and DRPLA mouse models, treatment with histone-deacetyltransferase (HDAC) inhibitors (sodium butyrate, 4-phenylbutyric acid sodium salt, and suberoylanilide hydroxamic acid) was shown to ameliorate neurotoxicity [ 41 44 ].…”
Section: Protein Toxicity In the Nucleusmentioning
confidence: 99%
“…The observations that disruption of individual Atg genes only partially suppresses Cut overexpression effects on C-I md neuron dendritic growth and filopodial-like terminal branching and that overexpression of Atg1 alone is insufficient to fully rescue cut loss-of-function dendritic defects in C-III md neurons can be explained in light of recent studies demonstrating that Cut functions via a variety of cellular processes in regulating dendritic development [ 3 ]. Recent neurogenomic studies demonstrate that Cut positively regulates the expression of hundreds of genes in md neurons [ 36 ] and functional studies have implicated molecules involved in cytoskeletal regulation [ 36 , 43 , 57 , 58 ], secretory pathway function [ 23 , 59 ], cell adhesion [ 39 ], and ribosomal regulatory function [ 36 ] as downstream effectors of Cut-mediated dendritic growth and branching, including the formation of dendritic filopodial-like terminal branches characteristic of C-III md neurons. These previous findings, coupled with our current results implicating autophagy, reveal that Cut exerts complex transcriptional effects on a broad spectrum of cellular processes that converge to promote dendritic diversity in md neurons and regulate terminal dendritic branching.…”
Section: Discussionmentioning
confidence: 99%